Gold nanohole arrays with ring-shaped silver nanoparticles for highly efficient plasmon-enhanced fluorescence - Sy-Hann Chen; Wu-Jui Hsieh; Yi-Wen Hong; Hung Ji Huang; Li-Ming Chiang; Tsung Sheng Kao; Min-Hsiung Shih; Hai-Pang Chiang (Results in Physics, 2023)
To enhance the interaction between electromagnetic fields and reduce photoluminescence (PL) lifetime in plasmon-enhanced fluorescence, this study presents a novel approach involving the fabrication of gold (Au) nanohole arrays (ANA) decorated with ring-shaped silver nanoparticles (AgNPs) on a silicon-dioxide (SiO2)/silver (Ag) substrate. The surface plasmon resonance coupling in terms of the PL reactions of ANA substrates with and without ring-shaped AgNPs is investigated via experiments and numerical simulations. The remarkable enhancement of PL intensity of the proposed substrate is attributed to increased absorption, which enables the tuning of surface-enhanced electromagnetic fields. Specifically, the Raman signal of rhodamine 6G (R6G) dye and the PL intensity of 4-(dicyanomethylene)-2-t-butyl-6-(1,1,7,7-tetramethyljulolidyl-9-enyl)-4H-pyran (DCJTB) molecules are significantly enhanced 3.7 and 2.2 times, respectively, compared to those of the bare ANA substrate. Meanwhile, the PL lifetime is reduced by 46.15%. These results confirm that ANAs decorated with ring-shaped AgNPs can significantly improve plasmon-enhanced fluorescence. The findings presented herein demonstrate the potential to revolutionize biosensing, imaging, and photonics.